ENHANCING ECONOMIC WELL-BEING OF CUSTODIAL INMATES THROUGH VOCATIONAL SKILLS ACQUISITION PROGRAMMES IN KATSINA STATE, NIGERIA - Abba, Mannir; Alkali, Muhammad (Sokoto Educational Review, 2021)
This study focussed on enhancing the economic well-being of custodial inmates through Vocational Skills Acquisition (VSA) programmes in Katsina State, Nigeria. Two research questions and one null hypothesis guided the study. A descriptive survey research design was adopted for the study. The population of the study was 762 inmates in the 11 correctional custodial centres in Katsina State at the time of the study out of which a sample of 351 respondents comprising all the 266 male convicted inmates and 85 female convicted inmates of the Katsina central correctional centres were deliberately selected for the study. The instrument used for data collection was a self-structured questionnaire tagged “Questionnaire on Enhancing Economic Well-being of Custodial Inmates through Vocational Skills Acquisition Programmes (QEEWOCITVSAP)”. The instrument was subjected to face validation by three experts. The reliability index of the research instrument was 0.80. The data collected for the study were analysed using descriptive statistics of mean and standard deviation, while the null hypothesis was tested using the t-test at the probability of 0.05 level of significance. The findings of the study revealed among others that there were inmate trainees in the Katsina central custodial centre and most of them have benefited from the VSA programme by acquiring skills that enhanced their economic well-being during and after incarceration. Based on these findings, the study recommended among others that, the Nigerian government should introduce and extend more VSA programmes for inmates in the custodial centres of the state. Also, governmental and non-governmental organisations and other stakeholders should be encouraged to provide the much-needed support for effective integration of discharged inmates into society and enhancing their economic well-being in the state and country at large.